Chitosan Immobilized on Saponite Surface in Extraction of V(V), Mo(VI) and Cr(VI) oxoanions - T. M. Budnyak; V. A. Tertykh; E. S. Yanovska (Хімія, фізика та технологія поверхні)
Chitosan-saponite composite has been obtained by crosslinking of adsorbed on saponite surface biopolymer with glutaraldehyde. The structure of composite was studied by IR-spectroscopy, concentration of immobilized chitosan was estimated using thermogravimetric analysis. The adsorption of microquantities of V(V), Mo(VI), and Cr(VI) oxoanions by obtained composite, initial natural mineral and polymer has been studied from aqueous solutions. The sorption capacities and kinetics adsorption characteristics of the composite adsorbent were estimated.